Determination of the frequency of four pathogenic variants causing inborn errors of metabolism in the western cape black population, using a multiplexed arms pcr approach - Dalmacio, Ronald (Department of Pathology, 2024)
Background: Carrier frequency determination of repeatedly identified pathogenic variants causing inborn errors of metabolism will enable early diagnosis and treatment of illness, and counselling of prospective parents. Four single nucleotide variants (SNV) were identified in our black South African population, on two or more separate alleles, namely, c.484C>T(p.Arg162Ter) in the GALNT3 gene causing hyperphosphataemic familial tumoral calcinosis (HFTC); c.803G>A(p.Arg268His) in the OXCT1 gene causing Succinyl-CoA:3-ketoacid CoA transferase (SCOT) deficiency; c.189G>A(p.Trp62Ter) in the G6PC gene causing glycogen storage disease type 1a (GSD 1a), and c.159dupT(p.Asp54*) in the BOLA3 gene causing multiple mitochondrial dysfunction syndrome type 2 (MMDS 2). Analysing large population cohorts for all four variants individually is time-consuming and expensive. Therefore, a simple, cost effective, and robust method like multiplexed ARMS PCR using standard PCR chemistry is attractive for use in resource constrained environments in which common population variants account for most of the disease burden. Methods: ARMS PCR primers were designed to detect the four variants of interest. Individual PCR methods were optimised for each primer pair, followed by an attempt to combine these reactions in a multiplex assay. A multiplex ARMS PCR method designed to detect both the BOLA3 and OXCT1 pathogenic variants listed above was used to screen a cohort of 750 samples, followed by Sanger sequencing to confirm findings in positive cases. Results: Individual PCR reactions performed well for all primer pairs at 54°C annealing temperature. Attempts to combine all four primer sets into a single multiplex reaction repeatedly failed. A smaller multiplex assay containing primers for the BOLA3 and OXCT1 variants showed promise initially, but Sanger sequencing failed to confirm the positive OXCT1 results found in all 14 ARMS PCR positive cases identified. Conclusions: This study investigated the feasibility of using multiplexed ARMS PCR to screen for multiple variants simultaneously in a clinically unaffected cohort. This study highlights the challenges of combining PCR reactions. Troubleshooting is laborious, time-consuming and may delay obtaining frequencies. The carrier frequency of the four IEM causing variants investigated in this study requires individual PCR assays, unless multiplex assays are optimised, or other methods are used.